2006
DOI: 10.1088/0022-3727/39/18/022
|View full text |Cite
|
Sign up to set email alerts
|

Modelling infiltration by means of a nonlinear fractional diffusion model

Abstract: The classical Richards equation describes infiltration into porous soil as a nonlinear diffusion process. Recent experiments have suggested that this process exhibits anomalous scaling behaviour. These observations suggest generalizing the classical Richards equation by introducing fractional time derivatives. The resulting fractional Richards equation with appropriate initial and boundary values is solved numerically in this paper. The numerical code is tested against analytical solutions in the linear case. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
69
0
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 30 publications
2
69
0
16
Order By: Relevance
“…The theoretical and experimental scientists observed that certain materials admit anomalous, fractional behavior, as [4]. There are many systems which evolution is governed by some fractional differential equations (for example, [5]). Fractional calculus is nowadays a broad and interesting field of very active research (see [6][7][8][9][10][11][12]).…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical and experimental scientists observed that certain materials admit anomalous, fractional behavior, as [4]. There are many systems which evolution is governed by some fractional differential equations (for example, [5]). Fractional calculus is nowadays a broad and interesting field of very active research (see [6][7][8][9][10][11][12]).…”
Section: Introductionmentioning
confidence: 99%
“…A lei de Darcy (originalmente aplicada ao estudo de fluxos em meios saturados) pode ser utilizada para meios insaturados e, a partir da mesma, se pode construir a equação de Richard (ER) clássica [2] como:…”
Section: Introductionunclassified
“…Nosso objetivo mais básico aquié o de estudarmos as consequências do uso da generalização fracionária da equação de Richard, seguindo os trabalhos de Pachepsky [4] e Gerolpymaton [2], em comparação aos modelos clássicos de ordem inteira. Numa etapa subsequente pretendemos realizar o mesmo estudo num contexto de derivadas fracionárias chamadas locais ou fractais [3], utilizando com dados obtidos através de medidas realizadas em solos do Brasil.A lei de Darcy (originalmente aplicada ao estudo de fluxos em meios saturados) pode ser utilizada para meios insaturados e, a partir da mesma, se pode construir a equação de Richard (ER) clássica [2] como:onde C(θ)é a difusividade da mistura em função do conteúdo volumétrico deágua θ.Usando a condição inicial: θ(0, x) = θ 1 , se x = 0, θ 0 , se x > 0 , podemos reformular a ER clássica como uma equação integral: …”
unclassified
See 1 more Smart Citation
“…There are many systems which evolution is governed by some fractional c 2013 Diogenes Co., Sofia pp. 559-572 , DOI: 10.2478/s13540-013-0036-5 differential equations (for example, [5]). Fractional calculus is nowadays a broad and interesting field of very active research.…”
Section: Introductionmentioning
confidence: 99%